A COMPARATIVE EXPOSITION OF THE LAW OF HUSBAND AND WIFE IN TERMS OF ISLAMIC LAW, SOUTH AFRICAN LAW AND THE LAW OF ENGLAND AND WALES ‒ PART TWO - Razaana Denson (Obiter, 2021)
The article discusses and compares the dissolution of a marriage as well as the legal consequences thereof in Islamic law, South African law and English law. This is done in order to demonstrate that despite similarities, there are vast differences between the three legal systems. This impacts on how Muslim personal law (MPL) can be recognised and regulated in South Africa and in England and Wales as constitutional democracies. South Africa, England and Wales share a commitment to human rights and have adopted various approaches in respect of accommodating the application of Islamic law. Internal pluralism also exists within the Muslim communities in South Africa, England and Wales as the majority of Muslims in these countries have to varying degrees developed diverse strategies to ensure compliance with Islamic law, as well as with South African and English law. Notwithstanding the accommodation of MPL in terms of South African and English law, the differences between these legal systems have resulted in decisions that, while providing relief to the lived realities of Muslims, are in fact contrary to the teachings and principles of Islam and therefore problematic for Muslims.